2019
DOI: 10.1002/lary.28483
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Fluorescence‐Guided Surgery for Sinonasal Cancer Using an Antibody‐Dye Conjugate

Abstract: Endoscopic resection of sinonasal squamous cell carcinoma has become the standard of care, but challenges remain in obtaining clear resection margins. The current study evaluated the feasibility of endoscopic fluorescence-guided surgery (FGS) to improve surgical resection in a human sinus surgical model. Methods: A fluorescence endoscope optimized for near-infrared (NIR) fluorescence detection was evaluated in a phantom study. Various endoscope diameters (4 and 10 mm) and viewing angles (0, 30, and 45 degrees)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Although there has been growing enthusiasm for the use of ICG and targeted agents with older robotic fluorescence imaging systems, 59 the rapid emergence of improved hardware, software, and technologies such as autofluorescence lifetime imaging and augmented reality have demonstrated significant potential for improved imaging during transoral robotic surgery 60 . Furthermore, preclinical studies using panitumumab IRDye‐800CW suggest potential for fluorescent guidance through transnasal endoscopic approaches for sinonasal squamous cell carcinoma 61 . With ongoing development and testing of new fluorescent agents, in combination with technological advances in near‐infrared fluorescence imaging software and hardware, there is likely to be higher sensitivity to tracers and the ability to quantify fluorophores in situ , furthering the incentive for utilizing fluorescence‐guided minimally invasive approaches for guiding head and neck procedures 62 …”
Section: Resultsmentioning
confidence: 99%
“…Although there has been growing enthusiasm for the use of ICG and targeted agents with older robotic fluorescence imaging systems, 59 the rapid emergence of improved hardware, software, and technologies such as autofluorescence lifetime imaging and augmented reality have demonstrated significant potential for improved imaging during transoral robotic surgery 60 . Furthermore, preclinical studies using panitumumab IRDye‐800CW suggest potential for fluorescent guidance through transnasal endoscopic approaches for sinonasal squamous cell carcinoma 61 . With ongoing development and testing of new fluorescent agents, in combination with technological advances in near‐infrared fluorescence imaging software and hardware, there is likely to be higher sensitivity to tracers and the ability to quantify fluorophores in situ , furthering the incentive for utilizing fluorescence‐guided minimally invasive approaches for guiding head and neck procedures 62 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, we dissected an apron flap for total laryngectomy in 11 patients (84.6%; No. [3][4][5][6][7][8][9][10][11][12][13]. Microvascular defect reconstruction was necessary in 7 patients (53.8%).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Non-invasive methods to characterise mucosal changes of the head and neck region, such as narrow-band imaging, confocal laser imaging, optical coherence tomography and fluorescence endoscopy, have been emerging recently [1][2][3][4] . One method that has shown a potential advance regarding its broad application outside of experimental studies is confocal laser endomicroscopy (CLE), which has demonstrated its value in the fairly similar oesophageal, gastric and intestinal epithelium in a wide range of clinical applications [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In a preclinical model, the role of fluorescence endoscope optimized for near-infrared fluorescence detection has been evaluated. This tool has been proved able to detect tumors marked through intravenous injection of an anti-EGFR monoclonal antibody conjugated to a fluorophore with an adequate tumor to background ratio [20]. Furthermore, radiofrequency ablation seems to offer an optimal bleeding control with a minimal thermal damage to adjacent neural structures [21].…”
Section: Surgical Resectionmentioning
confidence: 99%